2020
DOI: 10.18502/kss.v4i6.6648
|View full text |Cite
|
Sign up to set email alerts
|

How Do School Facilities Affect School Quality? Case Study in Vocational High School at Pati, Indonesia

Abstract: The study aims to determine about how does school facilities affect school quality at vocational high school in Pati, Central Java, Indonesia. The approach and methods used in the study was evaluation research using a discrepancy model. The data were collected by observation, interview, and documentation. Meanwhile, the analysis used interactive model by Milles and Huberman. The results showed that the school facility at vocational high school in Pati is up to standard of Regulation of National Education Minis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
1
Order By: Relevance
“…Thus, Omar, Zahar, and Rashid [18] emphasized that vocational education in Malaysia is given primary importance to enhance the students' vocational skills as the future builders of the country. The findings also agree with the conclusion of Octavia [7] that school facilities/equipment's presence leads to an improvement in teachers' and students' performance in terms of safety, action, participation in learning, and growth in achieving success. Moses [8] described the lack of adequate funding and support of the instructional programs as one of the shortcomings in the educational system in Uganda that must be addressed right away because of its effect on the students.…”
Section: Resultssupporting
confidence: 88%
“…Thus, Omar, Zahar, and Rashid [18] emphasized that vocational education in Malaysia is given primary importance to enhance the students' vocational skills as the future builders of the country. The findings also agree with the conclusion of Octavia [7] that school facilities/equipment's presence leads to an improvement in teachers' and students' performance in terms of safety, action, participation in learning, and growth in achieving success. Moses [8] described the lack of adequate funding and support of the instructional programs as one of the shortcomings in the educational system in Uganda that must be addressed right away because of its effect on the students.…”
Section: Resultssupporting
confidence: 88%
“…Hasbullah, et al, (2011), in their study, confirmed that there is a correlation between comfortable facilities and the level of students' performance. Meanwhile, learning media is a component of learning resources, containing instructional materials that make learning fun and stimulate students to learn (Octavia, Ismiyati., & Sholikah, 2020;Turi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the National Education System Law No. 20 of 2003 states that education has functions to develop the ability and build nation characters (Octavia., et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pendidikan merupakan kebutuhan mutlak yang harus dipenuhi sepanjang hayat (Octavia, Ismiyati, & Sholikah, 2020). Hal yang sama tercantum dalam Undang Undang Republik Indonesia Nomor 20 Tahun 2003 Tentang Sistem Pendidikan Nasional bahwa pendidikan berfungsi untuk mengembangkan kemampuan dan membentuk watak serta peradaban bangsa yang bermartabat dalam rangka mencerdaskan kehidupan bangsa.…”
Section: Pendahuluanunclassified